"An idea is in your body": Technology and transformation in the early childhood classroom. Issue 2 (June 2018) - Bentley, Dana Frantz
What does it mean to engage in transformational learning with young children? In a time when "technology" is hallowed as all-important, how do we frame young children as empowered, critical thinkers around technologies, instead of just consumers? This article looks closely at a child-centered, emergent curricular process within an early childhood classroom. Framing the "having of ideas" as the essential technology in children's lives, a teacher chronicles and analyzes children's idea-having process and the pedagogies around it. Focusing on children's talk, questioning, critique, and negotiation, this article shifts away from notions of traditional technologies, looking closely at the transformational learning inherent in children's collective having-of-ideas.